Aplikasi Pemasaran Perumahan Paradise Park Residence pada PT.Farabi Global Konstruksi menggunakan Metode Incremental - Aris, Aris; Kurniawathy, Dian; Yulistiani, Octavia (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
he property company PT. Farabi Global Construction is currently focusing on marketing the Paradise Park Residence housing, in addition to continuing to innovate to produce buildings, shophouses and other housing that is beneficial to the community. Problems occur when the existing housing marketing system is ineffective which causes sales to customers to continue to decline and therefore a marketing system is needed that facilitates the sale of housing units via the internet and Web-based. The method applied in this research is to apply the Incremental method in the form of a Software Development Method based on needs, with the Top-Down Decoupling standard. Besides that, UML is also used with Visual Paradigm, PHP, Discovery Testing, etc. to support research. The results of this research are Web-based Marketing Applications for Paradise Park Residence housing with the aim of increasing housing sales that can be implemented at PT. Farabi Global Construction.